Optimalisasi Penomoran Rumah Dan Kaveling Serta Pemetaan Blok Di RW 7 Wonorejo Rungkut Kota Surabaya - Patriadi, Andi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This community service activity discusses the problem of irregular house and plot numbering in RW 7 Wonorejo, Rungkut, Surabaya, which complicates the process of address finding by couriers and guests. The purpose of this service activity is to optimize the numbering and block mapping system to facilitate navigation and location identification. The methods used include aerial photography with drones, data processing with mapping and GIS software, discussions with the head of RW, as well as grouping and numbering of buildings. The result is the creation of a more accurate and detailed map, with systematic street naming and more orderly building numbering. The success of this activity is measured by the increase in efficiency in address finding and the satisfaction of residents with the new numbering system. However, there are weaknesses in the integration of the map with Google Maps and accessibility for all layers of society. The conclusion of this activity is the importance of integrating mapping technology in urban management, with recommendations for further integration with Google Maps and improving map accessibility for all layers of society. This activity demonstrates the great potential of mapping technology in improving navigation efficiency and urban community management.